Petrography and geochemistry of a Zn-Pb mineralization hosted in a dolostone, Puesto Gregor, Neuquen, Argentina (Latin American Journal of Sedimentology and Basin Analysis, 2021)
In Neuquen Basin, Argentina, a Zn-Pb mineralization was first reported by Garrido et al. (2000). The ore occurs in a carbonatic level located in Puesto Gregor, 50 km SSE from the city of Zapala at 39°11'34'' S, 69° 59'18'' W (Fig. 1). The hosting bed, a dolostone, belongs to a carbonatic-siliciclastic sequence of Lajas Formation, which is part of the Cuyo Group, Jurassic age.In the mineralization of Pb-Zn deposits associated to dolostones, the fluids that were involved in the ore precipitation process were also related to the dolomitization of the carbonatic rock (Warren, 2000). In this contribution, field, petrographic and geochemical studies were carried out in order to determine the temperature and composition of the dolimitizing fluids. The obtained results were then compared to those obtained from Carbon and Oxygen isotopes (Garrido et al., 2001) to discuss the dolimitization process.The mineralized bed, 0.90 m thick, outcrops for about 300 m along the strike (W-E) and 60 m in the dip direction (Fig. 2). This bed pinches out toward the east and toward the west it is no longer visible, it is covered by scours. Petrographic studies determined that the host rock is a dolostone with a breccia texture that becomes more siliciclastic towards the east grading thus to a fine sandstone with carbonatic cement. The hypogenic mineralization, mainly sphalerite, low quantities of galena, pyrite and marcasite is found within the small fractures. Some ghosts of fossils are still visible, but pervasive dolomitization characterizes the horizon. Two distinct dolomites are recognized by crosscutting relationships: a fine to medium grained crystalline dolomite, and a coarse grained crystalline dolomite related to the mineralization. The former shows dark-orange and white crystals which occur as patches or partially filled vugs. These crystals are 120-400 mm in size and exhibit subhedral to anhedral shapes (Fig. 3). According to Sibley and Gregg (1987), the texture is no planar -a- unimodal to polimodal. The latter dolomite presents well developed crystals (> 5 mm); they are translucent with pink color and pearl shine and have crystal faces that look like a pavement and is referred as "saddle" dolomite according to Radke and Mathis (1980). This "saddle" dolomite is found into dissolution cavities or as clusters of crystals located on the wall fractures; it is always associated to the mineralization.Chemical analysis of major, traces and rare earth elements are homogeneous throughout the bed. Mean values are 15% MgO, 29,66% CaO and 40,43 % CO2, with high MnO and Fe2O3 contents. The molar percentages of CaCO3 and MgCO3 indicate near stoichiometric ratio (52% and 48%) with a light excess of Ca (Table 1, Fig. 4). The trace elements Sr, Na, Fe and Mn are used to constrain dolomite evolution. Sr values varies from 79 to 159 ppm and Na from 74 to 225 ppm; Mn and Fe contents are higher than the values determined for carbonatic rocks (Turekian and Wedepohl, 1961). ÓREE and LREE contents are low, and the diagram normalized to chondrite shows a negative anomaly of Eu and a great negative anomaly of Ce.The 13C (VPDB) and 18O (VPDB) values vary from -2,9 to -9 ‰ and from -2,6 to -4 ‰ respectively (Table 2). The 13C are incoherent with the data recorded for Jurassic marine carbonates (near 0 ‰) while 18O values can be correlated with carbonates of the same age (Veizer et al., 1999).Petrography and chemical analysis allow characterizing the depositional environment of the Zn- Pb mineralized dolostone. The xenotopic texture of the dolomite with no planar crystals, gives evidence that the temperatures of deposition should have been higher than 50-60°C (Gregg and Sibley, 1984). On the other hand, the chemical composition, near ideal dolomites (stoichiometric ratio), indicates slow crystallization at high temperature (Morrow, 1982). Moreover, the destructive fabric and the homogeneous composition suggest a high temperature dolomitization (Machel, 2004).Trace element values, mainly Na and Sr, agree with burial dolomites, as well as the fluid inclusions reported for these samples by Cesaretti et al. (2002). The negative Ce anomaly indicates that these rocks were formed in a marine environment. Two different processes of carbonate precipitation can produce negative Ce anomaly (Möller, 1989; Bau and Möller, 1992): deposition from seawater or from hydrothermal solutions equilibrated with highly oxidized sediments. The latter is discarded because of the presence of framboidal pyrite and organic matter, which, along with the Eu negative anomaly indicates that the dolimitization were generated under euxinic conditions. This dolostone is in contact with anoxic mudstones (Los Molles Formation, Cuyo Group).Petrographic and geochemical criteria reflect that the dolomitization was caused by normal or modified sea water in a burial environment at temperatures above 140ºC. In burial or altered dolostones, the oxygen isotopes reflect temperature of precipitation and isotope composition of the dolomitizing fluids. The oxygen isotope values of this dolomitized bed are compatible with the isotope composition of carbonates precipitated from sea water at 25°C. The narrow range in the obtained values indicates that there was no influence of meteoric water during this process (Allan and Mathews, 1982). The homogeneous values of 18O isotope suggest that the physic-chemical conditions remained constant during dolomitization, what is in agreement with the textural and geochemical homogeneity found in the study samples. The 18O isotope values of a fluid equilibrated with carbonate at 140°C indicate that the fluid belongs to a basinal fluid.The 13C isotopes reflect an organic origin for the carbon. This carbon came from the diagenesis of organic matter caused by an increase in temperature during the burial of the basin (Garrido et al., 2001; Cesaretti et al., 2002).In contrast with other MVT deposits of the world, in Puesto Gregor, the dolomitization was a slow process acting at high temperatures, what has been confirmed by the homogeneity of the fabric and the narrow range in the isotope and trace elements composition. These conditions were reached during burial of the basin where the rocks interact with the basin fluids associated with the ore minerals.
Keywords: Dolostone; Zn-Pb sulphide minerals; Petrography; Geochemistry; Puesto Gregor; Neuquen Basin.